CERMINAN FEMINISME DALAM NOVEL THE BEST OF ME KARYA NICHOLAS SPARKS - MANDEY, APRILIA WIDYA; WANTASEN, ISNAWATY L.; MARENTEK, ANDRIYANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis Skripsi is entitled Cerminan Feminisme dalam novel The Best of Me karya Nicholas Sparks. The objectives of this research were to identify, analyze and describe the feminism as well as to analyze how women fought the struggle with women power in The Best of Me by Nicholas Sparks. The writer based her research on the theory of Betty Friedan (1963). According to Friedan, there are five concepts of feminism that consist of The Suburban Women, The American Women, The Educated Women, The Happy Women, and New Women. In conducting this study, the writer used intrinsic and extrinsic approaches, and qualitative analysis in which the process consists of describing, analyzing, and interpreting process. Intrinsic element was used to analyze and identify the characters, and the extrinsic element was used to analyze and describe the types of feminism. These approaches were applied in order to get the appropriate analysis and to answer the problems. The results of this research were the description of events to know Amandaâ€™s characters, the woman who struggled and fought with her power based on the five concepts of feminism by Betty Friedan (1963).Â Keyword: Feminism, Character